"You start by changing the whole cultural context": aikido v. gender violence. Issue 5 (3rd September 2019) - Ganoe, Kristy L.
ABSTRACT: Aikido is a martial art that focuses on non-violent approaches to conflict. The current article discusses ways that experienced practitioners of aikido adjust the social environments in which they practice this leisure pastime in order to pre-emptively address gender violence. Their approaches compliment the tactics of bystander intervention and community accountability strategies. This study is based on data obtained through naturalistic observations, participant observations, and interviews (n = 15) with people who had been studying aikido for an average of 12.4 years. Interventions were conducted at the levels of policy, leadership, curriculum, and game structure. The collection of modifications to aikido practitioners' social environments includes resistance to binary opposition between two sexes, social hierarchies, violence against the self, homophobic talk, and suppression of empathy.